Electrocorticographic and neurochemical findings after local cortical valproate application in patients with pharmacoresistant focal epilepsy - (:unkn) unknown (WILEY, 2020)
Because oral pharmacological treatment of neocortical focal epilepsy is limited due to common systemic side effects and relatively low drug concentrations reached at the epileptic foci locally, application of antiepileptic agents directly onto the neocortical focus may enhance treatment tolerability and efficacy. We describe the effects of cortically applied sodium valproate (VPA) in two patients with pharmacoresistant neocortical focal epilepsy who were selected for epilepsy surgery after a circumscribed epileptic focus had been determined by invasive presurgical evaluation using subdural electrodes. Local VPA modified epileptic activity as electrocorticographically recorded from the chronic focus in both patients. In addition, VPA induced local increase of the inhibitory neurotransmitter gamma-aminobutyric acid (GABA) in cortical tissue samples, whereas the excitatory glutamate was possibly decreased. In this clinical pilot study, we could show antiepileptic effects of cortically applied VPA in humans by electrocorticographic and neurochemical parameters.
Keywords: electrocorticography; human; local pharmacotherapy; neocortical focal epilepsy; sodium valproate; gamma-aminobutyric acid (GABA); NEOCORTICAL SEIZURES; RAT-BRAIN; GLUTAMATE; PHARMACOTHERAPY; DELIVERY